Influence of circadian time and age on glomerular angiotensin II receptors in normotensive Sprague-Dawley and transgenic hypertensive TGR(mREN2)27 rats - Lemmer, Björn; Rueff, Thomas; Reiter, Sabine; Huser, Lutz; Hauptfleisch, Stefan; Witte, Klaus (Chronobiology international, 2001)
In male heterozygous transgenic hypertensive rats, TGR(mREN2)27 (TGR), exhibiting an inverse blood pressure profile and in normotensive Sprague-Dawley (SPRD) controls, the density and affinity of angiotensin II receptors were determined at six circadian times in glomeruli of animals 11 weeks old kept under light-dark 12h:12 (LD 12:12) conditions. Angiotensin II receptors were also studied in rats 18-20 weeks old of both strains at 2h after light onset. As a measure of renal excretory functions, diuresis, creatinine, and protein excretion were monitored using metabolic cages. The expression of angiotensin II receptor mRNA was determined in renal arteries 2h-4h after light onset. The following results were obtained: Renal excretory functions showed significant daily variation, with higher excretion rates in the dark span in both TGR and SPRD rats. No circadian phase dependency was found in the glomerular angiotensin II receptors in both rat strains. However, receptor density was significantly lower in TGR than in SPRD rats. In both strains, receptor number increased with aging. In renal arteries, the angiotensin II receptor mRNA of the main receptor subtype AT1A was neither strain nor age dependent, AT1B- and AT2-receptor mRNAs were significantly lower in TGR than SPRD rats. In conclusion, the results demonstrate that the overactive renin-angiotensin system in TGR rats led to a down-regulation of glomerular angiotensin II receptors that was not accompanied by a down-regulation of the mRNA of the dominant AT1A- receptor subtype. Circadian short-term variations in blood pressure in both TGR and SPRD rats are not reflected by daily variation in angiotensin II receptor density of renal glomeruli or by variation in receptor expression in renal vascular tissue.
Published online: 07 Jul 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 11.04.2022